Sex differences in the brain : the relation between structure and function : proceedings of the 13th International Summer School of Brain Research, held at the Royal Netherlands Academy of Arts and Sciences, Amsterdam, the Netherlands, 22-26 August 1983 - Vries, Gerrit Jacob de; Bruin, J. P. C. de; Uylings, H. B. M. (Harry B. M.); Corner, M. A. (Michael Alan), 1933- (Progress in brain research, 1984)
SEX DIFFERENCES IN THE BRAIN.